Pedagogical management system (sgp) and school evaluation: the influence of a technology on the pedagogical coordinator’s action - Silva, Claudia Gonçalves da; Santos, Ricardo dos (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
This work aims to address the influence of the Pedagogical Management System (SGP) - a technological tool for pedagogical registration used by the Municipal Education Network of the City of São Paulo - in the actions of the Pedagogical Coordinators in front of the school evaluation. A bibliographic study was carried out on evaluation for learning, the role of the Pedagogical Coordinator in relation to the evaluation activities, the technological resources as facilitators of the school evaluation actions and the functionalities existing in the SGP. In addition, a field research was done with Pedagogical Coordinators of elementary schools of the Municipal Network of São Paulo. In a junction between technology and pedagogy, the present work contributes to the reflection on the quality of teaching, addressing the bias of school evaluation, with emphasis on learning for all students.